Uncommon Presentation of COVID-19 in Pediatric Patients: Anosmia - Dağlı, Hatice Y.; Akcan, Özge M.; Pekcan, Sevgi; Gençeli, Mustafa; Özdemir, Hüseyin S.; Uğurlu, Betül; Özbek, Ümmü S.; Parlatan, Havva; Akın, Fatih; Yazar, Abdullah; Kılıç, Ahmet O.; Özdemir, Mehmet; Taşbent, Fatma E. (Journal of Pediatric Infectious Diseases, 2021)
Objective The novel coronavirus disease 2019 (COVID-19) infection was declared as a pandemic by the World Health Organization on March 11, 2020. Although the complaint of anosmia is well described in adult patients, there is limited knowledge in pediatric patients. We aim to evaluate the epidemiological characteristics and clinical findings of children with anosmia in COVID-19-positive pediatric patients.Methods Patients diagnosed with COVID-19 infection at 1 month to 18 years of age, who admitted to Meram Faculty of Medicine of Necmettin Erbakan University between March and June 2020, were retrospectively reviewed, and the patients who had anosmia or developed anosmia during follow-up were then included in the study. The diagnosis was established by polymerase chain reaction (PCR).Results A total of 71 patients were diagnosed with COVID-19 and 14 (19.7%) of them had anosmia. Mean patient age was 14.07 (range: 10–16) years. Six of our 14 (42.8%) patients had anosmia at the time of diagnosis and anosmia developed in the follow-up among eight patients. The mean duration of anosmia in our patients was 6.9 ± 3.8 days. Recovery time was 1 to 4 days in four patients (28.5%), 5 to 8 days in four patients (28.5%), and 9 to 14 days in six patients (42.8%).Conclusion In this article, it was emphasized that anosmia can be the sole manifestation or concomitant with other symptoms in children with COVID-19 disease. Care and attention is important to identify COVID-19 patients at an early stage of the disease and limit the spread of the virus.
Keywords: anosmia; COVID-19; polymerase chain reaction; children